2015
DOI: 10.1371/journal.pone.0120789
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New Genomospecies in the Mycobacterium terrae Complex

Abstract: Members of the Mycobacterium terrae complex are slow-growing, non-chromogenic acid-fast bacilli found in the natural environment and occasionally in clinical material. These genetically closely-related members are difficult to differentiate by conventional phenotypic and molecular tests. In this paper we describe the use of whole genome data for the identification of four strains genetically similar to Mycobacterium sp. JDM601, a newly identified member of the M. terrae complex. Phylogenetic information from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Upon BLAST analysis of the 16S rRNA gene (full) against the whole-genome shotgun contigs (wgs) database, a 99.9 to 100% match (0 to 1 bp) was achieved with 3 of 4 strains obtained from the trunk washes of captive elephants. These strains were described as new genomospecies within the M. terrae complex (56).…”
Section: Previous Reported Casesmentioning
confidence: 99%
“…Upon BLAST analysis of the 16S rRNA gene (full) against the whole-genome shotgun contigs (wgs) database, a 99.9 to 100% match (0 to 1 bp) was achieved with 3 of 4 strains obtained from the trunk washes of captive elephants. These strains were described as new genomospecies within the M. terrae complex (56).…”
Section: Previous Reported Casesmentioning
confidence: 99%
“…The phylogenetic tree ( Figure 1 ) shows four clusters belonging to nontuberculous mycobacteria grouped in the Mycobacterium terrae complex 23 . A hsp 65 gene dendrogram revealed three subclusters with 76.0% of genetic relatedness, particularly for M. engbaekii and M. arupense cluster, and for M. nonchromogenicum and M. heraklionense cluster (data not show).…”
Section: Resultsmentioning
confidence: 99%
“…However, while the capacity to produce distinct viral sequence bins would undoubtedly improve interpretation of holobiont-derived viral metagenomes, a recent investigation into viral metagenome binning confirmed that coverage-based binning methodologies are not appropriate for amplified viral samples (Smits et al, 2015 ). Tetranucleotide frequency binning has been used in several metagenomics analyses to identify discrete microbial bins (Swingley et al, 2012 ; Delmont et al, 2015 ; Moreira et al, 2015 ; Ngeow et al, 2015 ). However, this method requires contigs of at least 5kb for reasonable accuracy (Dick et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%